Heartland : a historical drama about the internment of German-Americans in the United States during World War II - Simon, Lojo; Simons, Anita (Social fictions series., 2014)
During World War II, the US government confined thousands of Japanese-, German- and Italian-Americans to isolated, fenced and guarded relocation centers known as internment camps. At the same time, it shipped foreign Prisoners of War captured overseas to the US for imprisonment. Heartland reflects on the intersection between these two historic events through the story of a German-born widow and her family who take in two German Prisoners of War to work their family farm. But the German-American family and the POWs bond too well for the townspeople to accept, and the widow is arrested, interned and eventually suffers a breakdown, which tears her family apart. Based on true stories, Heartland illustrates what can happen when fear and prejudice pit neighbor against neighbor in times of war. A dramatic tale that grants insights into American history, Heartland is a winner of the Dayton Playhouse FutureFest and a runner-up for the Kennedy Center American College Theatre Festival David Mark Cohen National Playwriting Award. The story is shocking; for me it was revelatory, wrote theatre critic Pat Launer. Deporting our own citizens, Who knew? But the play, while conveying historical information, is not in the slightest didactic. It's a family story, a tale of survival and acquiescence, of racism, of neighbor against neighbor. Not a pretty picture. While it may be read for pleasure, Heartland also is a useful tool for exposing students to important lessons in history, politics, economics, sociology, psychology, women's studies and other academic disciplines.